Opioid-free anesthesia: what about patient comfort? A prospective, randomized, controlled trial - Hontoir, S; Saxena, S; Gatto, P; Khalife, M; Ben Aziz, A M; Paesmans, M; Sosnowski, M (Acta anaesthesiologica belgica, 2016)
We investigated the effect of a pern-operative opioid-free approach on postoperative patient comfort in patients undergoing breast cancer surgery. From September 2014 to July 2015, 66 female patients of the Belgian Oncology Institut Jules Bordet were recruited. They were randomized into two groups: the first group received anesthesia with opioids for their breast cancer surgery, and the second group received opioid-free anesthesia. Patient comfort was evaluated 24 hours postoperatively through the QoR-40 score, with a difference of 15 points considered as being clinically relevant. Postoperative analgesia was provided through a piritramide patient-controlled analgesia device, during the first 24 hours. The hypothesis of this study was that opioid-free anesthesia would improve quality of recovery after anesthesia. A statistically significant difference in postoperative QoR-40 score was observed between groups [Mean (SD) QoR-40 of 182.1/200 (13.9) in the opioid-free group, and 175.6/200 (14.80) in the opioid group; P = 0.04]. The clinical relevance of this finding is questionable, insofar as the difference of 15 points was not met. A statistically significant difference in postoperative piritramide usage was observed (8.1 (6.6) in the opioid-free group, and 13.1 (9.4) in the opioid group; P = 0.03). This randomized controlled trial shows, for the first time, equal comfort during the immediate postoperative period in patients having received opioid-free and conventional anesthesia for their breast cancer surgery. Opioid-free anesthesia in this indication appears safe, and may be associated with slightly reduced pain during the first 24 postoperative hours.